DAYA PREDASI DAN RESPON FUNGSIONAL Curinus coeruleus MULSANT (COLEOPTERA; COCCINELIDE) TERHADAP Paracoccus marginatus WILLIAMS DAN GRANARA DE WILLINK (HEMIPTERA;PSEUDOCOCCIDAE) DI RUMAH KACA - Ginting, Tri Yaninta; bakti, Darma; Marheni, (Jurnal Online Pertanian Tropik, 2017)
Predation ability and functional respons of Curinus coeruleus Mulsant (Coleoptera ; Coccinelide) To Paracoccus marginatus (Hemiptera ; Pseudococcidae) in a greenhouse. The objective of the research was to know the predation ability of C. coeruleus to P.marginatus and functional response. This research was conducted from February to April 2017 in the greenhouse Faculty of Agriculture, University of Sumatera Utara Medan. The method used was Completely Randomized Design with and was held in 2 periods. The first period was Predation Ability Test and the second was the Functional response test. In Predation Ability Test there were one imagoes of C. coeruleus male and female which test with P. marginatus larvae instar II and instar III. In the Functional response test, there were one imagoes of C. coeruleus male and female which test with P. marginatus larvae instar II (from previous predation ability) with each of P. marginatus larvae differences was 5, 10, 15 and 20 P.marginatus imagoes. The results of this research showed that the highest Predation Ability percentage was showed on C. coeruleus female with 57.5% and the lowest was showed on C. coeruleus male with 20%. in Functional response test of C. coeruleus was showed on type I and low R with 0.5375.